(untitled) (Journal of Humanitarian and Applied Sciences, 2019)
The purpose of the present paper is to investigate the Fekete-Szego problem for certain new subclasses starlike and convex functions of complex of order denoted by and respectively, which involving certain a generalized derivative operator defined in [8]. Various known or new special cases of our results are also pointed out.